Strategi Investasi di Pasar Modal - Pakpahan, Kadiman (Journal the Winners: Economics, Business, Management, and Information System Journal, 2003)
Capital market is market for longtherm money instrument. This article describes about benefit, capital market instrumen, risk and strategy in capital market.